A new nomogram including total cerebral small vessel disease burden for individualized prediction of early-onset depression in patients with acute ischemic stroke - Zhou, Lihua; Chen, Licong; Ma, Linqing; Diao, Shanshan; Qin, Yiren; Fang, Qi; Li, Tan (Frontiers in Aging Neuroscience, 2022)
Objectives: The present study was designed to evaluate the effects of total cerebral small vessel disease (CSVD) on early-onset depression after acute ischemic stroke (AIS), and to develop a new nomogram including total CSVD burden to predict early-onset post-stroke depression (PSD). Methods: We continuously enrolled patients with AIS who were hospitalized at the First Affiliated Hospital of Soochow University between October 2017 and June 2019. All patients were assessed for depressive symptoms using the 17-item Hamilton Depression Scale (HAMD-17) at 14±2 days after the onset of AIS. The diagnosis for depression was made according to American Diagnostic and Statistical Manual of Mental Disorders Version 5 (DSM-5). The demographic and clinical data were collected including total CSVD burden. On the basis of multivariate logistic model, the independent factors of early-onset PSD were identified and the predictive nomogram was generated. The performance of the nomogram was evaluated by Harrell’s concordance index (C-index) and calibration plot. Results: A total of 346 patients were enrolled. When contrasted to 0 score of total CSVD burden, the score ≥2 (moderate to severe total CSVD burden) was an independent risk factor of early-onset PSD. Besides, gender, cognitive impairments, baseline Barthel Index (BI) and plasma fibrinogen were independently associated with early-onset PSD. The nomogram based on all these five independent risk factors was developed and validated with an Area Under Curve (AUC) of 0.780. Additionally, calibration plot revealed adequate fit of the nomogram in predicting the risk of early-onset depression in patients with AIS. Conclusions: Our study found the total CSVD burden score of 2 to 4 points was an independent risk factor of early-onset PSD. The proposed nomogram based on total CSVD burden, gender, cognitive impairments, baseline BI and plasma fibrinogen concentration gave rise to a more accurate and more comprehensive prediction for early-onset PSD.